2009
DOI: 10.1308/147870809x450584
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma presenting as peri-implantitis: a case report

Abstract: Dental implants have proved to be a useful adjunct in the rehabilitation of oral cancer patients. We describe the case of a 62-year-old woman who presented with a white patch in the oral cavity, diagnosed to be a squamous cell carcinoma. She underwent extensive surgery including microvascular reconstruction, followed by implant rehabilitation. Unfortunately, she suffered from multiple episodes of peri-implantitis and later on went on to develop oral squamous cell carcinoma around two of the dental implants. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 2 publications
0
29
0
11
Order By: Relevance
“…Peri-implantitis is known to affect 5-10% of osseointegrated dental implants. Peri-implant mucositis is a related inflammatory process that affects only the soft tissues and is reversible [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Peri-implantitis is known to affect 5-10% of osseointegrated dental implants. Peri-implant mucositis is a related inflammatory process that affects only the soft tissues and is reversible [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Son muy pocos los casos de carcinomas preimplantarios descritos en la literatura 2,3,9,12,[14][15][16][17] . A nuestro parecer una de las razones pudiera estar simplemente relacionada con el ejercicio habitual a nivel privado de la implantología.…”
Section: Discussionunclassified
“…La media de edad fue de 62 años, y en más de la mitad de los pacientes, se trataba de recidivas de carcinomas previos, tratados con resección marginal de mandí-bula o incluso mandibulectomías parciales o totales y rehabilitados para su función oral con implantes que fueron colocados de forma inmediata sobre la mandíbula remanente o sobre injertos autólogos 2,9,12,16 .…”
Section: Discussionunclassified
“…Fourteen studies, which did not comply by the eligibility criteria, were excluded (see Appendix). In total, 14 studies [11][12][13][14][15][16][17][18][19][20][21][22][23][24] were included and processed for data extraction, as shown in Table 1 RESULTS…”
Section: Search Strategymentioning
confidence: 99%
“…8 Similar results have been reported by other studies. 9,10 Although DI have been shown to exhibit high survival rates in patients having undergone oral cancer treatment, 1,[8][9][10] clinical studies [11][12][13][14][15][16][17][18][19][20][21][22][23][24] have also reported oral squamous cell carcinoma (OSCC) to arise after installation of DI. In their study, Gallego et al 16 presented a case report of an 81-year-old woman who had received dental implant therapy.…”
mentioning
confidence: 99%